코리네박테리움 맥긴레이 각막궤양 - 방소라(So Ra Bang), 안 민(Min Ahn), 조남천(Nam Chun Cho), 유인천(In Cheon You) (Daihan angwa haghoi jabji, 2019)
목적: 3개월 이상 결막염으로 치료받은 환자에서 발생한 Corynebacterium macginleyi에 의한 각막궤양 1예가 있어 이를 보고하고자 한다. 증례요약: 72세 여자가 좌안의 각막부종 및 혼탁의 진행으로 헤르페스각막염 의심하에 개인 안과에서 전원되었다. 내원 3개월 전부터 좌안의 결막 충혈과 통증을 호소하고 있었다. Levofloxacin 안약과 acyclovir 연고를 사용하고 있었다. 세극등현미경검사에서 각막상부에서 중앙에 이르는 5.4 × 4.0 mm 크기의 각막상피결손 및 기질 침윤과 함께 각막 후면의 침착물을 보여 그람 염색 및 배양검사를 시행한 결과, 결막과 각막 모두에서 그람 양성균이 검출되고 Corynebacterium macginleyi가 동정되었다. Vancomycin으로 점안치료한 후 3개월째에 각막에 경한 혼탁만을 남기고 완전히 치료되었다. 결론: 최근 결막 상주균인 Corynebacterium macginleyi가 결막염과 안검염의 주요 원인균으로 대두되고 있는데, 장기간 결막염을 앓은 환자에서 발생한 서서히 진행하는 각막염의 경우에는 원인균으로 Corynebacterium macginleyi를 고려해야 하겠다. Purpose: To report a case of a Corynebacterium macginleyi-infected corneal ulcer of a patient who had been treated for conjunctivitis for more than 3 months. Case summary: A 72-year-old female was transferred from a private ophthalmic clinic for evaluation of herpetic keratitis with progressive corneal edema and infiltration in the left eye. She had a history of conjunctival hyperemia and eyeball pain in her left eye 3 months prior to her visit. She was treated with levofloxacin eye drops and acyclovir ointment (Herpesid®, Samil, Co., Ltd. Seoul, Korea). On slit lamp examination, 5.4 × 4.0 mm corneal epithelial defects and stromal infiltrations were observed in the upper to central cornea, and endothelial keratic precipitates were found. Gram positive bacteria were detected on Gram staining and Corynebacterium macginleyi was identified on bacterial cultures from the conjunctiva and cornea. She was treated with topical vancomycin eye drops. After 3 months of treatment, the corneal ulcer was completely resolved, leaving mild superficial opacity on the cornea. Conclusions: While Corynebacterium macginleyi, normal flora of the conjunctiva, is considered a major causative agent for conjunctivitis and blepharitis, Corynebacterium macginleyi should also be considered a possible cause of slowly progressive keratitis in patients with chronic conjunctivitis. KCI Citation Count: 0